Multi-taxon biodiversity response to restoration of the riparian zone in coniferous plantation forest - Jonas Morsing; Kaj Sand-Jensen; Karsten Raulund-Rasmussen; Rouven Nagel; Simone Møller Zacho; Hans Henrik Bruun; Lars Baastrup-Spohr (Ecological Engineering, 2026)

Height growth and total volume production models for short rotation Paulownia plantations - Nick M. Merriman; Anders Taeroe; Thomas Nord-Larsen; Karsten Raulund-Rasmussen (Forest Ecology and Management, 2025)

Forest dynamics in LCA: Integrating carbon fluxes from forest management systems into the life cycle assessment of a building - Camilla Ernst Andersen; Inge Stupak; Endrit Hoxha; Karsten Raulund-Rasmussen; Harpa Birgisdóttir (Resources, Conservation and Recycling, 2024)

Continental mapping of forest ecosystem functions reveals a high but unrealised potential for forest multifunctionality - Fons van der Plas; Sophia Ratcliffe; Paloma Ruiz‐Benito; Michael Scherer‐Lorenzen; Kris Verheyen; Christian Wirth; Miguel A. Zavala; Evy Ampoorter; Lander Baeten; Luc Barbaro; Cristina C. Bastias; Jürgen Bauhus; et al. (Ecology Letters, 2018)
Humans require multiple services from ecosystems, but it is largely unknown whether trade‐offs between ecosystem functions prevent the realisation of high ecosystem multifunctionality across spatial scales. Here, we combined a comprehensive dataset (28 ecosystem functions measured on 209 forest plots) with a forest inventory dataset (105,316 plots) to extrapolate and map relationships between various ecosystem multifunctionality measures across Europe. These multifunctionality measures reflected different management objectives, related to timber production, climate regulation and biodiversity conservation/recreation. We found that trade‐offs among them were rare across Europe, at both local and continental scales. This suggests a high potential for ‘win‐win’ forest management strategies, where overall multifunctionality is maximised. However, across sites, multifunctionality was on average 45.8‐49.8% below maximum levels and not necessarily highest in protected areas. Therefore, using one of the most comprehensive assessments so far, our study suggests a high but largely unrealised potential for management to promote multifunctional forests.

Biodiversity and ecosystem functioning relations in European forests depend on environmental context - Sophia Ratcliffe; Christian Wirth; Tommaso Jucker; Fons van der Plas; Michael Scherer‐Lorenzen; Kris Verheyen; Eric Allan; Raquel Benavides; Helge Bruelheide; Bettina Ohse; Alain Paquette; Evy Ampoorter; et al. (Ecology Letters, 2017)
The importance of biodiversity in supporting ecosystem functioning is generally well accepted. However, most evidence comes from small‐scale studies, and scaling‐up patterns of biodiversity–ecosystem functioning (B‐EF) remains challenging, in part because the importance of environmental factors in shaping B‐EF relations is poorly understood. Using a forest research platform in which 26 ecosystem functions were measured along gradients of tree species richness in six regions across Europe, we investigated the extent and the potential drivers of context dependency of B‐EF relations. Despite considerable variation in species richness effects across the continent, we found a tendency for stronger B‐EF relations in drier climates as well as in areas with longer growing seasons and more functionally diverse tree species. The importance of water availability in driving context dependency suggests that as water limitation increases under climate change, biodiversity may become even more important to support high levels of functioning in European forests.

Fertilization of Willow Coppice Over Three Consecutive 2-Year Rotations—Effects on Biomass Production, Soil Nutrients and Water - Petros Georgiadis; Lisbeth Sevel; Karsten Raulund-Rasmussen; Inge Stupak (BioEnergy Research, 2017)

Is Tree Species Diversity or Species Identity the More Important Driver of Soil Carbon Stocks, C/N Ratio, and pH? - Seid Muhie Dawud; Karsten Raulund-Rasmussen; Timo Domisch; Leena Finér; Bogdan Jaroszewicz; Lars Vesterdal (Ecosystems, 2016)

Allometric Biomass, Biomass Expansion Factor and Wood Density Models for the OP42 Hybrid Poplar in Southern Scandinavia - Anders Taeroe; Thomas Nord-Larsen; Inge Stupak; Karsten Raulund-Rasmussen (BioEnergy Research, 2015)

Commercially Grown Short Rotation Coppice Willow in Denmark: Biomass Production and Factors Affecting Production - Thomas Nord-Larsen; Lisbeth Sevel; Karsten Raulund-Rasmussen (BioEnergy Research, 2015)

Does species richness affect fine root biomass and production in young forest plantations? - Timo Domisch; Leena Finér; Seid Muhie Dawud; Lars Vesterdal; Karsten Raulund-Rasmussen (Oecologia, 2015)

Erratum to: Fertilization of SRC Willow, II: Leaching and Element Balances - Lisbeth Sevel; Morten Ingerslev; Thomas Nord-Larsen; Uffe Jørgensen; Peter E. Holm; Kirsten Schelde; Karsten Raulund-Rasmussen (BioEnergy Research, 2014)

Fertilization of SRC Willow, II: Leaching and Element Balances - Lisbeth Sevel; Morten Ingerslev; Thomas Nord-Larsen; Uffe Jørgensen; Peter E. Holm; Kirsten Schelde; Karsten Raulund-Rasmussen (BioEnergy Research, 2014)

Fertilization of SRC Willow, I: Biomass Production Response - Lisbeth Sevel; Thomas Nord-Larsen; Morten Ingerslev; Uffe Jørgensen; Karsten Raulund-Rasmussen (BioEnergy Research, 2014)

The forest Gribskov, Denmark: lessons from the past qualify contemporary conservation, restoration and forest management - Mette Venås Overballe-Petersen; Karsten Raulund-Rasmussen; Rita M. Buttenschøn; Richard H. W. Bradshaw (Biodiversity and Conservation, 2014)